2022
DOI: 10.1109/access.2022.3166223
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Reconfigurable Antennas for 5G Wireless and CubeSat Applications: A Review

Abstract: The rapid development of wireless technology has sparked interest in multi-band reconfigurable antennas as devices and satellites are innovating toward miniaturization. With limited space, reliable and efficient high bandwidth antenna systems are needed for current and next-generation wireless technology as well as for the revolutionary small satellites. The fifth generation of mobile communication technology promises high data rates, low latency and good spectrum efficiency. One of the key enablers of this te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 133 publications
0
13
0
Order By: Relevance
“…A Planar Inverted F Antenna (PIFA)‐based MIMO antenna with VSWR 3 is presented in Padmanathan et al 13 to cover the cellular bands in the frequency range of 0.8–6 GHz. A detailed review of multi‐standard frequency agile antennas is reported in Ramahatla et al 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Planar Inverted F Antenna (PIFA)‐based MIMO antenna with VSWR 3 is presented in Padmanathan et al 13 to cover the cellular bands in the frequency range of 0.8–6 GHz. A detailed review of multi‐standard frequency agile antennas is reported in Ramahatla et al 14 …”
Section: Introductionmentioning
confidence: 99%
“…A Planar Inverted F Antenna (PIFA)-based MIMO antenna with VSWR 3 is presented in Padmanathan et al 13 to cover the cellular bands in the frequency range of 0.8-6 GHz. A detailed review of multi-standard frequency agile antennas is reported in Ramahatla et al 14 The reconfigurable antennas described above necessitate the inclusion of an active device in the antenna aperture, which results in radiation pattern distortion. To retain stable radiation characteristics with less distortion, filtering antennas with reconfigurable microstrip feedlines are widely adopted in the literature.…”
mentioning
confidence: 99%
“…Based on frequency or pattern reconfigurable technology, the communication system's filtering process can be easily controlled, and the number of utilized antennas can be reduced. Recent works on frequency reconfigurable antennas for 5G wireless and cubeSat application, pattern reconfigurable patch antennas for mid-band 5G applications, and flexible frequency-reconfigurable antenna for global system for mobile communication (GSM), fourth generation long-term evolution (4G-LTE), industrial, scientific and medical (ISM), and 5G Sub-6 GHz band applications can be found in [24][25][26], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of the LP antenna is only capable to detect signals in one direction and will face a polarization mismatch loss when the signal is curving from different angles [19]. Therefore, a circularly polarized (CP) antenna is preferable for various applications because it can receive a component of the signal persistently due to the angular variation, regardless of receiver orientation, thus making the CP antenna capable to transmit and receive signals in all planes so that the strength of the signals is not lost and transferred to another plane and is still used [20]. As a result, the gain and performances of the system can increase and the multipath effect can improve [21,22].…”
Section: Introductionmentioning
confidence: 99%